Green supply chain management and sustainable performance among certified manufacturing firms in Malaysia: the mediating effect of social capital - Che Sobry, Suheil (2022)
Recently, an increase in demand for green initiatives and matters of sustainability has required a paradigm shift for manufacturing firms to conduct their operations. Since manufacturing firms have often been charged for the environmental liabilities of their suppliers, Green Supply Chain Management (GSCM) was introduced to integrate environmental management practices within manufacturing firms with the suppliers and customers. The GSCM is also believed to be closely related to social capital through integration process and social relationships between partners in the supply chain. However, the number of GSCM studies considering the social capital approach, particularly empirical studies, remains limited. Therefore, this study was conducted to examine the mediating effect of social capital on the GSCM and sustainable performance linkage. A survey was conducted on ISO14001 Environmental Management System certified manufacturing firms in Malaysia. A total of 106 questionnaires were completed by the respondents and considered to be appropriate for the data analysis. The data was analysed using Partial Least Squares-Structural Equation Modelling (PLS-SEM). It was found that the GSCM’s internal environmental management and structural social capital are significantly correlated with sustainable performance while structural and relational social capital significantly mediate the relationship between the GSCM and sustainable performance. This study contributes to the body of knowledge through the introduction of social capital as it is still relatively new and offers a wide opportunity for an extension of GSCM research. The findings of this study would also be valuable in providing new insights to management into their environmental goals and sustaining successful performance within the pressures of stakeholders and environmental regulations. The value of model fit also suggested that other variables or external factors can be included for future research to improve the prediction of sustainable performance, such as company ownership, type of industry, or technology advancement as moderating variables.